Isolating the PGR signal in the GRACE data: impact on mass balance estimates in Antarctica and Greenland - V.R. Barletta; R. Sabadini; A. Bordoni (Geophysical Journal International, 2008)
Redistribution of mass over the Earth and within the mantle changes the gravity field whose variations are monitored at high spatial resolution by the presently flying GRACE space gravity mission from NASA or, at longer wavelengths, by the Satellite Laser Ranging (SLR) constellation. In principle, GRACE data allow one to study the time evolution of various Earth phenomena through their gravitational effects. The correct identification of the gravitational spatial and temporal fingerprints of the individual hydrologic, atmospheric, oceanographic and solid Earth phenomena is thus extremely important, but also not trivial. In particular, it has been widely recognized that the gravitational estimates of present-day ice mass loss in Greenland and Antarctica, and the related effect on sea level changes, depend on an accurate determination of the Postglacial Rebound (PGR) after Pleistocene deglaciation, which in turn depends on the assumed solid Earth parameters and deglaciation model. Here we investigate the effect of the uncertainty of the solid Earth parameters (viscosity, litospheric thickness) and of different deglaciation processes on PGR in Greenland and Antarctica. We find that realistic constraints to the trend in ice mass loss derived from GRACE data determine a range of variation substantially wider than commonly stated, ranging from an important ice loss of -209 Gt yr(-1) to an accumulation of +88 Gt yr(-1) in Antarctica, and Greenland ablation at a rate between -122 and -50 Gt yr(-1). However, if we adopt the set of most probable Earth parameters, we infer a substantial mass loss in both regions, -171 +/- 39 and -101 +/- 22 Gt yr(-1) for Antarctica and Greenland, respectively.